2008
DOI: 10.1158/1055-9965.epi-07-0058
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Effect on Oxidative Stress Is Independent of Change in Estrogen Metabolism

Abstract: Purpose: The effect of exercise training on lipid peroxidation and endogenous estrogens is not well understood in premenopausal women. Exercise effects on these variables could mediate observed associations of exercise with hormonally related cancers, including breast cancer. The purpose of the study is to determine the effect of 15 weeks of aerobic exercise on lipid peroxidation, endogenous estrogens, and body composition in young, healthy eumenorrheic women. Methods: Fifteen sedentary premenopausal women (18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 20 publications
3
31
0
2
Order By: Relevance
“…Consistent with a previous report (Schmitz et al, 2008), the present study found that the free F2-Isoprostanes in plasma were significantly lower following 8 weeks of exercise in obese and leptin responder normal-weight participants. However, some studies found decreased F2-Isoprostanes levels but only after acute excessive exercise (Nasca et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with a previous report (Schmitz et al, 2008), the present study found that the free F2-Isoprostanes in plasma were significantly lower following 8 weeks of exercise in obese and leptin responder normal-weight participants. However, some studies found decreased F2-Isoprostanes levels but only after acute excessive exercise (Nasca et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…However, the increase in ghrelin resulting from wheat fiber consumption was not associated with satiety [65]. The rise in plasma ghrelin for RAISIN and RAISIN + WALK were not expected given the increase in plasma leptin, as an inverse relationship between these variables usually exists [66]. However, it is possible that the elevation in circulating leptin decreased appetite for the subjects who consumed raisins, causing a reduction in food intake.…”
Section: Discussionmentioning
confidence: 94%
“…Vergleichbare Resultate werden auch aus mehreren nicht-kontrollierten Interventionsstudien berichtet, bei denen um 25 bis 34% erniedrigte F2-Isoprostankonzentrationen nach einem körperlichen Training über zwölf bis 15 Wochen gemessen wurden [53,54]. In einer randomisierten achtwöchigen Studie bei älte-ren Patienten mit Typ-2-Diabetes wurden hingegen keine signifikanten Effekte beobachtet [55].…”
Section: Wirkung Auf Den Oxidativen Stress Und Auf Dna-reparatur-mechunclassified